STUDI KANDUNGAN BAKTERI Salmonella sp PADA SATE KAMBING YANG DIJUAL DI KECAMATAN BUMIAYU KABUPATEN BREBES TAHUN 2014 - Elendea Windi Arfila; Priyo Santoso (Poltekkes Kemenkes Semarang, 2015)
Salmonellosis caused gastroenteristis (acute indigestion), the cause is Salmonella choleraesuisdan Salmonella enteriditis. Salmonellosis occur after an incubation time of 5-72 hours after eating foodcontaining Salmonella. Symptoms are abdominal pain, diarrhea, nausea and headache. Thepurpose of this study was to determine the presence or absence of Salmonella in goat sataysold in District of Bumiayu Subprovince of Brebes Year 2014.Research methodology that is used is descriptive, data that have been collected will becompared with the exist standard.Based on the results obtained, hygiene sanitation management satay at 6 places ranging from theselection of foodstuffs, foodstuff storage, food processing, transporting and serving food that the foodwas good with a score of 88.05%. Based on the examination of 6 samples in the laboratory goat sataycan be seen that 4 samples did not meet the standards because of the positive Salmonella while2 negative samples that meet the standards set are negative (zero).The conclusion of this research is the sanitation management of satay in six place with a scorethat is already a good 88.05%, and 6 samples of goat satay can be seen that 4 samples did not meet thestandards because of the positive Salmonella while the 2 sample negative Salmonella so as to meet thestandards that have been determined under National Agency for Drugs and Food ControlNumber.HK.00.06.1.52.4011, 2009 about the determining contamination maximum limination of microbaand chemistry on the food that is negative (zero). Suggestions can be given that the goat satay beconsumed should be completely cooked and when preparing food should refer to aspects of foodsanitation hygiene to prevent contamination.